Assessment of dental students' attitudes and perceptions toward professionalism - N Amritha; M K Vanishree; K Mahesh Chandra; Priya Babu (Wolters Kluwer Medknow Publications, 2019)
Background: Professionalism is a broad competency needed by dentists to act effectively and efficiently. It is seen as a central part of both undergraduate (UG) and postgraduate (PG) curricula. Aims: This study aimed to assess the attitude and perceptions of dental students toward professionalism and the influence of gender on the same. Materials and Methods: A cross-sectional descriptive study was carried out in four different dental colleges of Bengaluru city. A stratified random sampling technique was employed to select a sample of 480 dental students. The Professional Assessment Scale was used to assess professionalism. It is a 22-item questionnaire which is divided into three domains, namely, empathy and humanism, professional development and relationship, and professional responsibility domains. The students responded on a 5-point Likert scale, ranging from strongly disagree to strongly agree. The data collected were analyzed using SPSS software version 14.0. Chi-square test, independent Student's t-test, ANOVA, and Pearson's correlation were performed. P < 0.05 was considered statistically significant. Results: The mean overall Professional Assessment Scale scores were 93.12 ± 10.35, 97.41 ± 8.59, and 94.42 ± 10.06 for UGs, interns, and PGs, respectively, and these associations were statistically significant (P < 0.001). No significant gender differences were observed in the overall mean scores. Conclusions: The study concluded that all the participants possessed at least some elements of professionalism; recognizing these concerns and integrating them into professional educational programs can result in a better and more supportive health-care service for the public.